Set up database on criminal cases involving senior citizens — MCPF - Borneo Post, (KK) (Borneo Post, 2017)
Kota Kinabalu The authorities and members of the public should strengthen their collaboration to help reduce crime cases involving senior citizens, especially those who live alone.